Matharpacady-08.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
A bread seller ferrying his goods on a bicycle in front of D’Silva House, 24 Matharpacady, the house of Mr Trevor D’Silva, and his sister Joan Saint-Prix, grandnephew and grandniece to Joseph ‘Kaka’ Baptista (1864-1930), Indian freedom fighter and a prominent member of the East Indian community. Kaka Baptista was born in Matharpacady in 1864 in his ancestral house which has now been demolished and replaced by a high-rise building. Kaka Baptista was a barrister at the Bombay High Court and was closely associated with Bal Gangadhar Tilak. In 1925, he was elected as the mayor of the Bombay Municipal Corporation.